2011
DOI: 10.7196/samj.4523
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal deliveries - is there a need for documented consent?

Abstract: A pregnant woman nearing delivery, with an uncomplicated pregnancy and no immediate indication for caesarean section (CS), can either deliver vaginally or by CS. Historically CS has been viewed as more dangerous than vaginal delivery. However, CSs are far safer today and the complications of unmonitored labour are increasing, especially in the public sector.Delivery should be discussed during the antenatal period. The decision to have a CS is usually followed by signing an authorisation form -incorrectly refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
9
0
2
Order By: Relevance
“…An audit done by Naidoo and Moodley (2009) on a spe cialist private practice within KwaZulu Natal found that maternal requests, breech delivery, HIV and previous CSD contributed to the high CSD rates in that particular practice. Literature has further cited that fear of vaginal deli very, the need for control in the birthing process (Lavender et al, 2012;Dhai et al, 2011), convenience, and the preserva tion of the pelvic floor (Dhai et al, 2011) are some of the reasons why women opt for a CSD. Although CSD are consi dered relatively safe (Dhai et al, 2011), there are still a number of complications associated with this procedure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An audit done by Naidoo and Moodley (2009) on a spe cialist private practice within KwaZulu Natal found that maternal requests, breech delivery, HIV and previous CSD contributed to the high CSD rates in that particular practice. Literature has further cited that fear of vaginal deli very, the need for control in the birthing process (Lavender et al, 2012;Dhai et al, 2011), convenience, and the preserva tion of the pelvic floor (Dhai et al, 2011) are some of the reasons why women opt for a CSD. Although CSD are consi dered relatively safe (Dhai et al, 2011), there are still a number of complications associated with this procedure.…”
mentioning
confidence: 99%
“…Literature has further cited that fear of vaginal deli very, the need for control in the birthing process (Lavender et al, 2012;Dhai et al, 2011), convenience, and the preserva tion of the pelvic floor (Dhai et al, 2011) are some of the reasons why women opt for a CSD. Although CSD are consi dered relatively safe (Dhai et al, 2011), there are still a number of complications associated with this procedure.…”
mentioning
confidence: 99%
“…Anthony and colleagues 12 challenge the suggestion by Dhai et al 13 that that there are strong ethical and legal imperatives for a practitioner to obtain authorisation for modern 'medicalised' vaginal delivery. Unchallenged, these views carry serious implications for overburdened public sector facilities.…”
Section: Dhai Et Al Challengedmentioning
confidence: 94%
“…Doctors will tend to 'focus on a hypothetical court case, which in turn may affect the quality of the care that is delivered' . [3] There are signs that this may be occurring already: this country has an abnormally high caesarean section rate, ranging from 20% to 30% in the public sector to nearly 60% in the private sector, [10] and there is a documented increase in pathology costs due to increased utilisation. [11] The editorial in this issue [2] advises doctors in this 'increasingly hostile, pressurised and uncertain' practice climate to ensure that they have insurance or indemnity (see box, p. 460) and that their provider has experience of managing claims in SA.…”
Section: South African Medical Journalmentioning
confidence: 99%